THE IMPLEMENTATION OF INDEPENDENT LEARNING BY STUDENTS OF ENGLISH LANGUAGE EDUCATION STUDY PROGRAM - Gracevania Sukma Harianita (Widya Mandala Surabaya Catholic University, 2024)
This paper reports on a study that aims to find out the extent to which the students of English Education Study Program implemented Independent Learning. This study is qualitative in nature employing phenomenological approach. Independent Learning involves individuals’ planning, self-monitoring, controlling and evaluating their learning activities. The participants of this study were students of the English Language Education Study Program of a private university in Surabaya. The implementation of Independent Learning by the students participated in this study was analysed based on those activities involved in Independent Learning. A questionnaire was used to collect data. The result of this study revealed that the extent to which the students implemented Independent Learning varied. The majority of the students did not do complete activities supposedly involved in Independent Learning. Only a few of them did self-monitoring and evaluation of their learning activities.